Rasionalitas Mahasiswa Menggunakan Pinjaman Online - Aditya, Dimas; Utami, Diyah (Paradigma, 2025)
The development of the internet in Indonesia is increasingly rapid. This development has undoubtedly led to social transformation. This social transformation, which has led to social change, refers to changes in payment activities usingdigital technology. The increasing use of financial transactions via the internet also impacts the fulfillment of society'sneeds. Students, as agents of change, play a strategic role in driving scientific, technological, and socioeconomic progress. However, amidst the high expectations placed on students, they face significant challenges, particularly financial ones. The presence of online loans undoubtedly impacts students' financial needs. Therefore, this study aims to examinestudents' experiences when using online loans. This study also utilizes James S. Colomen's Rational Choice Theory. The research method used is qualitative, with data collection techniques including observation and interviews, whichwill be analyzed using Illness Narrative analysis techniques. The results of this study indicate that students' rationalityinusing online loans varies widely and is influenced by value orientations, pressures of circumstances and time, andlifechallenges faced. Keywords: Online Loans, Students, Rational Choice